How important are snow transport and sublimation for the mass balance of Antarctica? - Sigmund, Armin; Brito Melo, Daniela; Sharma, Varun; Huwald, Hendrik; Lehning, Michael (2022)
This presentation is part of the session 'Contributing to climate science through research in polar and high-altitude regions: the early-career researchers' point of view' in the Geneva Cryosphere HUB of the COP26 conference. We discuss the mass balance of Antarctica and explain how the modelling of snow transport by the wind and associated sublimation can be improved. These efforts may contribute to better estimates of sea level rise.